Spiritual Healing: Ragam Bahasa Balian Sebagai Salah Satu Pelestarian Tradisi Lokal di Bali - Susanti, Luh Eka; Kesumayathi, Ida Ayu Gayatri; Ekasani, Kadek Ayu; Agastia, I Gede Made Aditya (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This research aims to identify the language varieties of Balian and the factors that influence these language varieties. This research is descriptive qualitative with a linguistic and pragmatic theory approach used by Balian. Data collection was done by in-depth interviews with Balians in the hotel. The collected data were then transcribed and thematically coded to identify patterns in language use, such as the use of language, the use of metaphorical language styles, and the sentence structure used. The results found that the balian language variety when communicating with clients is the use of affirmative language, the use of spiritual metaphor style, and the use of imperative sentence structure to direct the client's experience and emotional response during the healing process. Meanwhile, the factors that influence balian language varieties are cultural, spiritual, social, economic, and personal factors. An understanding of these factors helps explain how balians navigate between local traditions and the needs of their clients, as well as how they integrate different elements of language to create effective and meaningful healing experiences. Future studies go more in-depth into analyzing balian language use when viewed pragmatically and therapeutically.